Type 1 or type 2 diabetes : has the ship already sailed? - Amy E., Morrison; Sim, Sing Yee; Marie-France, Kong; Rob, Gregory (Association of British Clinical Diabetologists, 2021)
Introduction Type 1 diabetes is an autoimmune condition characterised by loss of pancreatic beta cells and therefore insulin production. C-peptide, secreted in equal amounts to insulin, can be used to assess beta cell function, the concentration being reflective of endogenous insulin production.1